Modeling Gamification in Online Stores with an Interpretive Structural Approach - Raheleh Jalalniya; Fatemeh Eidi (‫مدیریت بازرگانی, 2019)
Objective The ultimate objective of the research is to determine how to use the scientific approach to achieve gamification in the e-commerce. Given the importance of gamfication in today's business market and the unique role that the brand plays in the field of e-commerce, identifying the dimensions of gamification and its impact on e-market is a key factor toward the success of organizations in the field of e-commerce. Therefore, this study aimed at investigating the underlying factors of gamification in online stores.   Methodology The present study is an applied research in nature and is a descriptive survey based on the nature and the method. Interpretive structural modeling method was used to analyze the research data. The statistical population of this research is comprised of managers and experts of Bamillo Online Store. The study used the views of 9 experts in the field of internet marketing and sales at Bamillo Online Store. Library methods were used to collect the literature and research backgrounds and the final data to investigate the effects of brand personality indices on B2B marketing were collected using a questionnaire.   Findings Based on the previous studies and specialized interviews, finally, the gamification indicators in online stores were identified including the  joy of using the system services, attractiveness of the game-like website design, enjoyable experience, amusement, user-firendly website design, the benefits of using game-based services, interacting with other users and social presence, awarding badges, building friendships, high interactive capability of the website, interacting with the system, feeling adventurous, stimulating user’s curiosity, success, comparing and competition with other users. In this study, after identifying the dimensions and indicators of the study, the relationships between the dimensions and the indicators identified using the concept of 'leading' were analyzed.   Conclusion The development of gamification can have a positive impact on the perceived enjoyment of users. It is suggested that in order to increase the positive impact on perceived enjoyment, the process or the product should be attractive and desirable by proposing appropriate incentives. Moreover, the non-lucrative and modest nature of the new design, compassionate services, online support and etc. can boost trust and give the consumer the feeling that the products are beneficial in this online store. This will ultimately improve the profitability of online stores.